Techno-economic analysis of providers’ profit using Ultra-density in 5G networks - Christos Bouras; Aikaterini Florou; Anastasia Kollia (20th Mediterranean Communication and Computer Networking Conference (MedComNet 2022), June 1 – 3, 2022, Paphos, Cyprus, 2022)
Fifth generation of mobile networks plays an important role internationally for the scientific community, as well as for everyday life. The challenges are rising, therefore, it is crucial to study technologies that can meet most requirements. Ultra-density is one of the technologies that appear to be a solution to the problems that arise. In this paper, authors present a techno-economic analysis of ultra-dense implementations and macrocellular deployments. In addition to structural analysis and benefits, authors develop economic models, based on parameters and factors that most affect these technologies. Furthermore, they conduct Sensitivity Analysis (SA) experiments based on those economic models, thus leading to important conclusions. Finally, there are proposals for future research and ways to reduce the higher costs of ultra-density.